Physical literacy in Indonesian school physical education: a systematic review of concepts, assessment, and implementation - Ridha, Sahbana; Mashud; Warni, Herita; Arifin, Syamsul (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Physical literacy (PL) is internationally recognised as a foundational concept in physical education, supporting lifelong engagement in physical activity. However, how PL is conceptualised, assessed, and implemented within Indonesian school contexts remains unclear, and no systematic synthesis of existing national research has been conducted. Objective: This study aimed to systematically review and synthesise empirical research on physical literacy in Indonesia, with particular attention to conceptual frameworks, assessment approaches, and implementation practices in school-aged populations. Methods: A PRISMA-guided systematic literature review was conducted using Scopus, PubMed, OpenAlex, Semantic Scholar, DOAJ, and Garuda databases. Studies published between 2020 and 2024 were screened, yielding 5,056 records, of which 20 met the inclusion criteria. Data were analysed using narrative synthesis across key thematic domains. Finding/Results: Most studies focused on primary school students and conceptualised physical literacy primarily through fundamental motor skills. Multidimensional PL frameworks encompassing motivation, confidence, knowledge, and lifelong engagement were rarely applied. Assessment methods were highly heterogeneous and lacked standardised, culturally adapted instruments. Although school-based interventions demonstrated short-term improvements in motor competence and physical activity, broader affective and cognitive dimensions of PL were largely neglected. Key challenges included limited teacher understanding of PL and the absence of explicit integration within the national curriculum. Conclusion: Physical literacy research in Indonesia remains fragmented and predominantly skill-oriented, with limited alignment to holistic PL principles. There is a clear need for culturally relevant frameworks, validated assessment tools, and strengthened teacher professional development. Future research should adopt comprehensive PL models and examine long-term, multidimensional interventions to better support children’s physical, cognitive, and affective development.